Clinical characteristics and caloric testing in patients with light or heavy cupula of the horizontal semicircular canal - Zhang, Xueyan; Xu, Jiao; Zhou, Tao; Yu, Xue; Xu, Jin; Yu, Heng; Song, Guangjie; Wei, Lingli; Yang, Xu; Hu, Mei; Chang, Liying (Frontiers in Neurology, 2025)
ObjectivesPersistent direction-changing positional nystagmus (DCPN) and null point (NP) are characteristic of cupulopathy of the horizontal semicircular canal (HSC). The cupulopathy can manifest as HSC-light cupula (HSC-Lcu) (geotropic DCPN) and HSC-heavy cupula (HSC-Hcu) (apogeotropic DCPN) in the supine roll test (SRT). Whether the affected side of cupulopathy could be based on the nystagmus intensity in the SRT is controversial. This study aims to explore the differences in clinical characteristics and the HSC function between the HSC-Lcu and HSC-Hcu.MethodsIn this retrospective study, the disease histories of patients were collected, including those of peripheral vestibular disorders, otological diseases, and neurological diseases. We compared the nystagmus characteristics and canal paresis (CP) between the two groups. A multivariable logistic regression analysis was performed to identify predictors of cupulopathy subtype classification.ResultsWe included 52 patients with HSC-Lcu (17 males; mean age: 66.6 years) and 47 patients with HSC-Hcu (24 males; mean age: 68.0 years). A history of sudden sensorineural hearing loss (SSNHL) was more common in patients with HSC-Lcu (n = 8) than in those with HSC-Hcu (n = 0) (p = 0.005). There was no significant difference in NP1, NP2, or NP3 between the groups. The NP2 is present in all patients with HSC-Hcu. The side with stronger nystagmus intensity during the supine roll test (SRT) was consistent with the NP side in 38 patients with HSC-Lcu and 21 patients with HSC-Hcu. CP was more frequent in patients with HSC-Lcu (n = 29) than in those with HSC-Hcu (n = 16) (p = 0.030). However, when evaluated within a multivariable logistic regression model, the presence of CP was not found to be statistically significantly associated with the outcome (p > 0.05).ConclusionA history of SSNHL specifically associates with HSC-Lcu, rather than HSC-Hcu. Determining the affected side of HSC-Lcu and HSC-Hcu based on nystagmus intensity during the SRT was unreliable. HSC-Lcu shows higher rates of CP, indicating that the function of HSC-Lcu was more impaired than that of HSC-Hcu. Clinicians should consider SSNHL history and perform caloric testing when evaluating suspected HSC-Lcu, and rely on the NP for lateralization.